Obmejne regije in Evropa - Mlinar, Zdravko (Teorija in praksa, 1996)
The future of border regions is traced both in terms of the general long-term regularities of socio-spatial restructuring as well as in terms of the involvement of regional actors concerning the management of the region's openness. Two dimensions of restructuring particularly are elaborated which both provide a challenge for a more autonomous and active role of these subjects: 1. the shift from contiguous, areal to network linkages and 2. the extension from region as a single unit to multilevel power-sharing. Historicaland geographical features are determining the variation in the rate and modes of taking part in the processes of European integration. The legacy of the zero sum game - in terms of shifting rather than opening borders - influences the strategy of opening border regions from the point of view of distrust and confidence-building. Non-parity roles represent another limiting factor. Both are exemplified in the experience gained in Istria (Croatian, Slovenian, Italian part of) and Euroregions on the Czech - German border.
Keywords: regije; regionalizem; autonomy; avtonomija; Europe; Evropa; Istra; Istria; obmejno sodelovanje